El delito de apología del terrorismo y la modalidad de compartir una publicación apologética - Canlla Mas, Patty Liliana (2025)
This article addresses a problem that directly impacts our criminal justice system, specifically the terrorism subsystem. This is the lack of uniformity in the criteria of criminal courts regarding the classification of the crime of apology for terrorism when the conduct consists of sharing a post on social media containing apology content created by a third party. This situation has generated and continues to generate contradictory rulings, which undermines confidence in the administration of justice. In this context, some courts issue sentences for this crime, while others acquit the defendant of the charges. Therefore, this research proposes that the Supreme Court put an end to the controversy, clearly ruling for or against considering this type of conduct as criminal conduct.